Marketing Techniques in Management of Enterprises Engaged in Tourism - Lomova, Lyudmila A.; Shiryaev, Dmitry V.; Kobersy, Iskandar S.; Borisova, Anna A.; Shkurkin, Dmitry V. (International Review of Management and Marketing, 2016)
Tourism is regarded as the service industry and it is one of the largest and dynamic economic sectors. Being engaged in tourism, tourism enterprises have to solve a lot of challenging problems, such as to find a market, retain or win new customers, to solve what to do in services, what means to use for competing, etc. Not so long ago these actions in Russian travel companies have had subjective and routine nature and have not brought positive long-term results. The current business completely rejects the ideology of passive market presence. The marketing activity is becoming more and more important for Russian travel companies because both social-economic and political factors of our society have dramatically changed. Instead of centralized planning we have freedom of entrepreneurial initiative, instead of constant commodity and service deficiency there is their excessive supply, and instead of government monopoly there is tough competition among commodity producers. Marketing involves a lot of various activities including marketing researches, product development, its distribution, price fixing and advertising. The major purpose is investigation of the above-mentioned activities in order to make the marketing functioning of tourism enterprises the most effective. Keywords: marketing, management, tourism, marketing management JEL Classifications: L83, Ðœ20, Ðœ31